Penguatan Karakter Religius Peserta Didik di Era Digital melalui Perspektif Pendidikan Agama Islam menurut Kajian Literatur - Mutiara Nabila; Ukhty Mumtaza; Zulista Sukma; Musthafa Rahman; Miftahir Rizqa (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study aims to analyze the strengthening of students' religious character in the digital age through a literature review based on the perspective of Islamic Religious Education. Digital transformation has changed the patterns of interaction, access to information, and behavior of students, so that religious education is required to present new approaches that are relevant and adaptive. Through a literature review method, this study examines classical and contemporary Islamic Religious Education theories, empirical study results, and scientific articles discussing moral guidance amid technological developments. The analysis results show that religious character includes the dimensions of faith, worship, morals, and social aspects that must be instilled through systematic and contextual education. The challenges of the digital era, such as exposure to negative content, religious misinformation, and instant culture, require the integration of ethical digital literacy and Islamic values. The role of PAI teachers has proven to be very strategic in guiding, assisting, and directing students to be able to use technology in a healthy and morally valuable manner. Teacher role modeling, the use of educational digital media, and continuous mentoring are key factors in the successful formation of religious character. In addition, systemic support from schools, families, and education policies is necessary for the character-building process to be consistent. This study emphasizes the importance of holistic religious guidance that is based on Islamic values and in line with the demands of the digital age. Keywords: Digital literacy; Digital ethics; Islamic Religious Education; Religious character; Sustainable behavior.